Adsorption of congo red dye from aqueous solutions by prepared activated carbon with oxygen-containing functional groups and its regeneration - Ridha Lafi; Imed Montasser; Amor Hafiane (Adsorption Science & Technology)
This study investigates the potential use of activated carbon prepared from coffee waste (CW) as an adsorbent for the removal of congo red dye from aqueous solution. The oxygen-containing groups of activated carbon prepared from CW play an important role in dyes ions adsorption onto activated carbon prepared from CW. The activated carbon is characterized by scanning electron microscopy and Fourier transform infrared (FTIR) spectroscopy. Adsorption experiments were carried out as batch studies at different contact time, pH, and initial dye concentration. The dye adsorption equilibrium was attained after 120 min of contact time. Removal of dye in acidic solutions was better than in basic solutions. The adsorption of dye increased with increasing initial dye concentration. The equilibrium data were revealed that Langmuir model was more suitable to describe the congo red adsorption and demonstrated excellent reusability potential with desorption greater than 90% throughout six consecutive adsorption–desorption cycles. Experimental data founded that kinetics followed a pseudo-second-order equation. Thermodynamic study showed that the adsorption was a spontaneous and exothermic process. According to the FTIR analyses, hydrogen bonding and electrostatic interactions between dyes and oxygen-containing functional groups on activated carbon prepared from CW are dominant mechanisms for dye adsorption.